Analyzing the Influence of Policy Networks on the Quality of Public Policy in West Java Province (2024–2025) (International Journal of Economics and Management Research, 2025)
Policy networks are an important factor in improving the quality of public policy, as they involve interaction and collaboration between the government, Non-Governmental Organizations (NGOs), the private sector, academics, and the public. This study aims to analyze the influence of policy networks on the quality of public policy in West Java Province in the 2024–2025 period. A quantitative approach was used with survey methods and multiple linear regression analysis, supported by documentation studies and semi-structured interviews. The results of the study indicate that limited collaboration between actors, uneven distribution of resources and information, variations in the capacity of non-governmental actors, and weak coordination and communication mechanisms are the main obstacles that affect the effectiveness, innovation, and responsiveness of public policy. This study concludes that strengthening policy networks through collaborative forums, increasing actor capacity, sustainable coordination mechanisms, regulatory simplification, and collective learning can improve the quality of public policy. These findings provide theoretical contributions to the study of policy networks as well as practical recommendations for more effective and participatory governance.